Analysis and improvement on identity-based cloud data integrity verification scheme - Shaohui WANG; Xiaoxiao PAN; Zhiwei WANG; Fu XIAO; Ruchuan WANG (Tongxin xuebao)
Many individuals or businesses outsource their data to remote cloud.Cloud storage provides users the advantages of economic convenience,but data owners no longer physically control over the stored data,which introduces new security challenges,such as no security guarantees of integrity and privacy.The security of two identity-based cloud data integrity verification schemes by Zhang et al and Xu et al respectively are analysed.It shows that Zhang et al.’s scheme is subjected to secret key recovery attack for the cloud servers can recover user’s private key only utilizing stored data.And Xu et al.’s scheme cannot satisfy security requirements of soundness.Based on Xu et al.'s scheme,a modified identity-based cloud data integrity verification scheme is proposed.A comprehensive analysis shows the new scheme can provide the security requirements of soundness and privacy,and has the same communication overhead and computational cost as Xu et al.’s scheme.